Peningkatan Kapasitas UMKM Kebon Alam Ecoprint melalui Pelatihan Business Model Canvas dan Strategi Pemasaran Omnichannel di Lakarsantri Surabaya - Yayu Sriwahyuni Hamzah; Utami Puji Lestari; Eko Nurmianto; Alfiah Indasah; Feby Salma Ayu Safitri (Pusat Riset dan Inovasi Nasional, 2025)
This Abdimas activity aims to enhance the capacity of Kebon Alam Ecoprint UMKM in Lakarsantri, Surabaya through training on the Business Model Canvas (BMC) and omnichannel marketing strategies. The main problems faced by the partner are the absence of a structured business plan and limited ability to integrate offline and digital marketing strategies. The method applied in this program is Participatory Action Research (PAR), which combines research and social intervention by actively involving the community throughout all stages of the activity. Using a community-based empowerment approach, the program emphasized active collaboration between the service team and the target community through focus group discussions (FGD), socialization, training, and mentoring in designing BMC and applying cross-channel marketing strategies. The results indicate an improvement in UMKM’s understanding of comprehensive business model mapping, the identification of ecoprint product value propositions, and the optimization of digital marketing channels integrated with offline sales activities. The tangible impacts of this program include a shift in entrepreneurial mindset toward digital adaptability, improved competitiveness, and the establishment of business independence. Thus, BMC training and omnichannel marketing strategies have proven effective in fostering the sustainability of creative economy-based UMKM.